2016
DOI: 10.1175/jas-d-15-0132.1
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Study of Convection in a Condensing CO2 Atmosphere under Early Mars-Like Conditions

Abstract: Cloud convection of a CO 2 atmosphere where the major constituent condenses is numerically investigated under a setup idealizing a possible warm atmosphere of early Mars, utilizing a two-dimensional cloudresolving model forced by a fixed cooling profile as a substitute for a radiative process. The authors compare two cases with different critical saturation ratios as condensation criteria and also examine sensitivity to number mixing ratio of condensed particles given externally.When supersaturation is not nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Our simulations show that the atmospheric domain is generally comprised of two characteristic regions -a relatively quiescent, stratified upper condensing region and a vigorously convecting lower dry region, separated by the first condensation level. This is similar to those found in 2D convection simulations of Yamashita et al (2016). We start with describing horizontal-mean properties of the simulations.…”
Section: Basic Structure and Dynamicssupporting
confidence: 81%
See 1 more Smart Citation
“…Our simulations show that the atmospheric domain is generally comprised of two characteristic regions -a relatively quiescent, stratified upper condensing region and a vigorously convecting lower dry region, separated by the first condensation level. This is similar to those found in 2D convection simulations of Yamashita et al (2016). We start with describing horizontal-mean properties of the simulations.…”
Section: Basic Structure and Dynamicssupporting
confidence: 81%
“…demonstrated the novelty on large-scale dynamics arisen from mass transport by precipitation and constraints from the condensation thermodynamics, then presented general circulation models (GCMs) in nondilute conditions. Yamashita et al (2016) performed two-dimensional convection modeling for a pure-CO 2 atmosphere in Martian conditions. Ding & Pierrehumbert (2018) further demonstrated the importance of horizontal heat transport in determining global surface temperature variation of pure-steam atmospheres.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the limitations of a one-dimensional model, (Listowski et al, 2014) showed that an additional source of condensation nuclei (CN) was required in the mesosphere. One study of cloud-resolving simulations on CO 2 condensation has been performed for the Early Mars climate (Yamashita et al, 2016), but none in the current conditions of Martian polar regions. Moreover, the respective roles of topography (Tobie et al, 2003;Colaprete and Toon, 2002) and convection (Colaprete et al, 2008) in driving cloud formation and snowfall in the polar regions remain to be determined, as does the coupling of CO 2 and H 2 O cycles through heterogeneous nucleation of CO 2 on H 2 O crystals.…”
Section: Introductionmentioning
confidence: 99%
“…A longstanding challenge in climate science is to improve the crude treatment of such convective phenomena in general circulation models, which hampers predictions of critical quantities such as changes in local precipitation and the sensitivity of Earth's climate to CO 2 . Looking beyond Earth, there is strong evidence that moist convection-that is, convection coupled to phase changes of a condensible substance-factors into the past and present evolution of the majority of solar system atmospheres, including Venus (Kasting 1988), Mars (Wordsworth 2016;Yamashita et al 2016), Jupiter (Gierasch et al 2000), Saturn (Li & Ingersoll 2015), the ice giants (Hueso et al 2020), and Titan (Schneider et al 2012). Therefore, in order improve our understanding of contemporary Earth's climate and planetary climates more generally, there is a clear need to deepen and generalize our understanding of moist convective physics.…”
Section: Introductionmentioning
confidence: 99%